2014
DOI: 10.11648/j.ijnfs.20140304.19
|View full text |Cite
|
Sign up to set email alerts
|

Development and Nutritional Evaluation of Infant Complementary Food from Maize (Zea Mays), Soybean (Glycine Max) and Moringa Oleifera Leaves

Abstract: Abstract:Aims: This study developed and evaluated infant complementary food made from locally available foods to which was feed to infants 6-12 months of age. The study was aimed to: develop infant complementary food from yellow maize (Zea mays), soybean (Glycine max) and green leafy vegetables (Moringa oleifera), determine the nutrient composition of the complementary food, determine the acceptability of the food and determine the nutritional quality of the infant complementary food in children. Study Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…In South India, the β‐carotene‐rich blue‐green alga Spirulina, prepared as a sweetened product suitable as a snack, improved vitamin A status of preschoolers attending daycare centers (Annapuma, Deosthale, & Bamji, ). Odinakachukwu, Nwosu, Ngozi, Ngozi, and Aloysius () revealed that Moringa oleifera fortification of infant complementary food improved its nutritional quality. Incorporation of pulverized M. oleifera leaves in infant foods could diversify food intake and ensure food and nutrition security.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In South India, the β‐carotene‐rich blue‐green alga Spirulina, prepared as a sweetened product suitable as a snack, improved vitamin A status of preschoolers attending daycare centers (Annapuma, Deosthale, & Bamji, ). Odinakachukwu, Nwosu, Ngozi, Ngozi, and Aloysius () revealed that Moringa oleifera fortification of infant complementary food improved its nutritional quality. Incorporation of pulverized M. oleifera leaves in infant foods could diversify food intake and ensure food and nutrition security.…”
Section: Resultsmentioning
confidence: 99%
“…In South India, the β-carotene-rich blue-green alga Spirulina, prepared as a sweetened product suitable as a snack, improved vitamin A status of preschoolers attending daycare centers (Annapuma, Deosthale, & Bamji, 1999). Odinakachukwu, Nwosu, Ngozi, Ngozi, and Aloysius (2014)…”
Section: Practices and Benefitsmentioning
confidence: 99%
“…Scholars have shown the potential of moringa in improving child nutrition (Odinakachukwu et al, 2014;Thierry et al, 2013). Moringa has also demonstrated the potential of improving vitamin A in serum depleted rats (Thurber and Fahey, 2009).…”
Section: Effect Of Lactic Fermentation Moringa and Pumpkin Fortificamentioning
confidence: 99%
“…This is largely responsible for the increasing researches on weaning food production, with the hope of increasing the protein content. Indeed, studies have documented the attempts by combining cereals with animal and plant proteins (Odinakachukwu, Ngozi, Ngozi, & Aloysius, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to fortify cereal with either plant or animal protein (Odinakachukwu et al, 2014). Fermented African locust beans (Parkia biglobosa) is an important source of plant protein and vitamin (Gernmah, Atolagbe, & Echegwo, 2007).…”
Section: Introductionmentioning
confidence: 99%